Molecular modifiers of T cell antigen receptor triggering threshold: the mechanism of CD28 costimulatory receptor. - Acuto, O; Mise-Omata, S; Mangino, G; Michel, F (2003)
CD28 was thought to represent a prototypic membrane receptor responsible for delivering the classically defined 'second signal' needed to avoid T cell paralysis when recognizing antigen presented by appropriate antigen presenting cells (APCs). Almost two decades after its molecular identification, the mechanism by which this 'second receptor' facilitates clonal expansion and differentiation upon antigen encounter is still not fully elucidated. There may be at least two reasons for this partially gray picture: the use of nonphysiological experimental conditions to study it and the fact that the action of CD28 may be partly masked by the presence of additional T cell surface receptors that also provide some costimulatory signals, although not equivalent to the one delivered through CD28. Thus, instead of aging, the study of CD28 is still a topical subject. What is appearing through work of recent years is that far from being purely qualitative, the CD28 signal provides a key quantitative contribution to potently boost the T cell antigen receptor (TCR) signal. In other words, CD28 is in part a signaling 'sosia' of the TCR. Also, it is clear now that CD28 operates via multiple molecular effects. Still, what we do not understand is the 'qualitative' part of this signal, perhaps due to lack of identification of unique signaling components and/or pathways activated by CD28 only. Here we review a series of recent findings pointing towards novel avenues to better understand the molecular basis of CD28 function.